Fluvio-lacustrine sedimentary processes and landforms on the distal Paraguay fluvial megafan (Brazil) - Lo, Edward L.; McGlue, Michael M.; Silva, Aguinaldo; Bergier, Ivan; Yeager, Kevin M.; de Azevedo Macedo, Hudson; Swallom, Meredith; Assine, Mario L. [UNESP] (Elsevier, 2019)
Tropical fluvio-lacustrine depositional processes along the toe of the Paraguay fluvial megafan were investigated with a focus on Lake Uberaba (LU), the largest lake in the Pantanal wetlands. A limnogeological analysis of LU was conducted using remote sensing imagery, lake water chemistry, sedimentological and radiochemical data from lake floor samples and short cores. Echo-sounding revealed that LU is deepest (Zmax = ~3.5 m) near its southern shoreline and outlet; the lake is hydrologically open throughout the year and is characterized by a dilute Ca+2-Na+-HCO3 − chemistry. Key environmental controls on sedimentation in LU include inflowing transverse and axial rivers and water level changes, which influence the composition, mixing, accumulation, and the organization of facies. Structureless brown sandy silts with relatively low organic carbon (TOCmean = ~1.7 wt%) and low to moderate biogenic silica (BiSimean = ~1.9 wt%) comprise most offshore lake floor sediments, whereas northern lake margin sediments consist of peaty silts and sandy silts whose origins are linked to inflowing Paraguay megafan distributary channels. Sediment core stratigraphy revealed that extant lacustrine deposits are underlain by oxidized clayey silts and sands, suggesting recent subaerial exposure of the basin floor. Sedimentary datasets conclusively suggest that LU is a shallow overfilled lake basin that is strongly influenced as a depositional system by its persistently open hydrology, shoreline channel density, and absence of margin coincident topography. This study provides new insights on lacustrine landform development in distal megafan settings, which is important for improving our understanding of fluvial landscapes.
Keywords: Distributive fluvial system; Lakes; Pantanal wetlands; Siliciclastic sediments